INTERCULTURAL COMMUNICATION IN ENGLISH CLASSES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the vital role of intercultural communication within English language classrooms. It emphasizes that English, as a global lingua franca, necessitates an understanding and appreciation of diverse cultural perspectives. The article provides practical examples of how intercultural communication can be fostered and highlights its benefits for language acquisition and global citizenship